Social Media Accounts of Food and Beverage Brands Have Disproportionately More Black and Hispanic Followers than White Followers - Rummo, Pasquale E. (Health Equity, 2021)
Introduction: On television, food companies promote their least nutritious products to Black and Hispanic youth more than White youth, but little is known about the extent to which Black and Hispanic adolescents may disproportionately engage with unhealthy food and beverage brands on social media relative to White adolescents. Methods: In 2019, we purchased and analyzed demographic data of social media users who followed 27 of the most marketed food/beverage brands on Instagram and Twitter. We used one-sample t-tests to compare percentages of Black, Hispanic, and White followers of the selected brands' accounts versus all social media accounts, and independent samples t-tests to compare followers of sugary versus low-calorie drink brands. We also used linear regression to examine associations between racially targeted marketing practices and the percentages of Black, Hispanic, and White followers on social media. Results: On Instagram, the percentage of Black followers of the selected brands (12.7%) was higher than the percentage of Black followers of any account (7.8%) (p<0.001). On Twitter, findings were similar for Hispanic users but opposite for White users. A higher racially targeted ratio was positively associated with the percentage of Black followers, and negatively associated with the percentage of White followers. Sugary drink brands had more Hispanic followers than low-calorie drink brands (p<0.001). Conclusions: Unhealthy food/beverage brands that target Black adolescents have a disproportionately higher percentage of Black followers on social media relative to White followers. These findings support the 2019 proposal to restrict racially targeted advertising through the Children's Online Privacy and Protection Act.